Impurity effective mass in superfluid ⁴He - Vakarchuk, I.O.; Babin, V.V. (Condensed Matter Physics, 1998)
The system of bose liquid + impurity is considered. The energy spectrum, as well as effective mass of impurity is calculated. For the case of an ³He atom in superfluid <⁴He numerical calculations are performed.